The Case for an IGAD Development Bank. (January 2019) - Michael, Bryane
Abstract: A multilateral development finance institution for the Inter-Governmental Authority on Development (IGAD) region represents the chance to create a strong pro-developmental actor—and energise the IGAD itself. Yet, senior IGAD officials will need to look beyond the traditional development banking model if they hope to make an impact of the scale needed to drag these poorest of countries out of poverty. In this article, the author argues for the design of a development bank modelled after successful role models—like the China Development Bank—instead of proven failures. A mix of government and private sector participation, a widely disbursed capital base and a temporary base in London will help ensure the proposed IGAD Communities Development Bank acts as bridge and vector of pro-developmental capitalism in the IGAD region.